Subjection of Religious Institutes to the Holy See - Grzegorczyk, Mateusz (Biuletyn Stowarzyszenia Kanonistów Polskich, 2024)
The ecclesiastical legislator grants religious institutes just autonomy so that they can carry out their mission, but this autonomy is not unlimited. This article explains the essence of this autonomy of religious institutes – both of pontifical right and diocesan institutes – while indicating and discussing their dependence on the Holy See. This interdependence is realised in such aspects as the approval of religious authorities, changes to constitutions and statutes, issues concerning the management of goods or broadly interpreted formation. An analysis of this research problem must factor in ecclesiological, juridical and teleological aspects of the subjection of religious institutes to the Holy See.